EFFECT OF ION CONCENTRATION OF SMART WATER ON OIL RECOVERY BY SPONTANEOUS IMBIBITION TEST - Shabrina Sri Riswati; Wisup Bae; Muslim Abdurrahman; Adi Novriansyah; Syamsul Irham; Dwi Atty Mardiana; Pauhesti (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2022)
Smart waterflooding has proven successfully improving oil recovery in numbers of laboratory and field scale applications. The phenomena behind the positive outcome is concluded to be wettability alteration. The smart water composition changes the wettability of the rock surface into partially water-wet, thus promoting a spontaneous imbibition of the aqueous phase and displacing the oil. However, there are some mechanisms causing the wettability alteration that have been proposed by researchers. The present study examines the oil recovery from spontaneous imbibition tests by modifying certain ion composition of the smart water. Prepared core samples with initial water and oil saturation were immersed in spontaneous imbibition cells filled with smart water and the oil recovered was monitored for some period of time. The predesigned smart water compositions consist of different ions concentration, i.e., Na+, Ca2+, and Mg2+, while maintaining identical total dissolved solid (TDS). The experimental results found that the ion composition of smart water affects the oil recovery regardless of the TDS, and low Ca2+ and Mg2+ concentrations shows the highest recovery factor.